The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3346/jkms.2017.32.5.764
|View full text |Cite
|
Sign up to set email alerts
|

Myxoid and Sarcomatoid Variants of Adrenocortical Carcinoma: Analysis of Rare Variants in Single Tertiary Care Center

Abstract: The aim of this study is to describe rare variants of adrenocortical carcinoma (ACC) and to compare the prognosis with that of conventional ACC. We retrospectively reviewed 8 cases of myxoid variant, 1 sarcomatoid variant, and 14 cases of conventional ACC, who underwent surgical resection at the Asan Medical Center between 1996 and 2014. An analysis of the clinicopathological characteristics, including the Weiss score, Ki-67 labeling index, and reticulin framework assessment is presented. The mean age of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
0
16
0
4
Order By: Relevance
“…Myxoid ACC is an uncommon variant of ACC and first reported by Tang and colleagues in 1979 in a 41-year-old woman [ 140 ]. Up to the year 2020, 47 cases of myxoid ACC have been reported in the literature [ 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ].…”
Section: Myxoid Adrenocortical Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Myxoid ACC is an uncommon variant of ACC and first reported by Tang and colleagues in 1979 in a 41-year-old woman [ 140 ]. Up to the year 2020, 47 cases of myxoid ACC have been reported in the literature [ 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ].…”
Section: Myxoid Adrenocortical Carcinomamentioning
confidence: 99%
“…Lipometaplasia were reported in 21% ( n = 5) of myxoid ACC [ 143 , 149 , 150 , 152 ]. The morphology is a reactive degenerative or metaplastic process in tumour cells which appears to be detected in myxoid ACC.…”
Section: Myxoid Adrenocortical Carcinomamentioning
confidence: 99%
“…These features could result in the difficulty of differential diagnosis, especially from metastatic adenocarcinoma to the adrenal gland [8,[20][21][22]. The majority of previously reported cases of myxoid ACC had clinical characteristics similar to those of conventional ACC, but Sung et al indicated that the presence of myxoid histological features in ACC was indeed associated with more aggressive clinical behavior and poorer overall survival than conventional ACC [9], which may explain the relatively aggressive biological course of our patient.…”
Section: Discussionmentioning
confidence: 91%
“…The myxoid variant of ACC was first reported in 1979 [19], and approximately 50 cases have been reported to date in the English-language literature to the best of our knowledge [9]. In the year 2017 World Health Organization classification, myxoid ACC was firstly recognized as the distinctive subtype of ACC [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation